Współfinansowanie rozwoju lokalnego z Europejskiego Funduszu Rozwoju Regionalnego w świetle projektów rozwojowych gmin województwa lubelskiego - Myna, Artur (Local Development Funding with ERDF in the Light of Development Projects of Gminas of the Lublin Voivodship, 2007)
The aim of the work is a presentation of absorption of European Regional Development Fund grants by gminas of the Lublin voivodship on the example of measure 3.1 - "Rural areas". In 2005, 113 rural and municipal-rural gminas (almost 60%) submitted applications for ERDF funding of local infrastructure development projects supported under this measure. Over 80% of ERDF grants will be used to finance construction of capital-consuming local roads and sewage systems. The total ERDF co-funding will exceed 70% of the value of gminas' development projects. Among 26 gminas, whose projects were approved to be co-financed, there are some municipalities with experience in using preaccesion funds.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 553-561